We Still Need to Improve Our Research Writing Ethics - Sehgal, Sheikh Arslan (Bangladesh Journal of Bioethics, 2016)
The aim of current effort is too sentient that the people should have to know what is happening and to explore the reasons behind the veil of reasons so they can generate and amend their opinions and deduce their own conclusions. The most worthy asset of a researcher is to publish valuable research and must first be earned the scientific professional integrity and then maintained it. The scientific community must obey the scientific ethical norms and rules if they want to play its due role. Still, we are bearing ethical quandaries in our research and we have to solve them for advancement of research in scientific community including Pakistan.